NON-VIOLENT PROBLEM SOLVING IN PIERRE MOREL'S B13: A SOCIOLOGICAL APPROACH - PRIDITYO, DEWAN (2010)
The objective of the study is to describe the B13 movie based on structural analysis and sociological analysis. This study is a qualitative study. The object of this study is B13 film directed by Pierre Morel's released in November 10, 2004. The data source is the B13 itself including the manuscript and film. The method of data collection is library research. The technique of data analysis is descriptive analysis. The researcher concludes the structural elements of B13 such as character and characterization, plot, setting, point of view, and theme are related one another and form a solid unity. This film includes some conditions such as crime, sport, power, common conflict, sadness. B13 begins with the political intervention of goverment to solve the problem as fast as he can. A simple trick with bom will do to get the final solution. In the ending two men make the change of that planing. The outcome of the study shows that the problem of B13 makes the conflict of govermential condition. So, it comes the bad solution of solving problem.